Genetic and molecular abnormalities in benign maxillomandibular odontogenic cysts and tumours: A review of the literature - Mamadou Diatta; Macoura Gadji; Babacar Tamba; Marie Jeo Dièmè; Bintou Catherine Gassama; Mouhammad Kane; Soukeye Dia Tine (Elsevier, 2021)
Introduction: Odontogenic lesions are diverse and varied. Some of them, in addition to having a significant power of bone destruction, recur most often after surgical removal. This could be explained by moleculoskeletal mechanisms that have not yet been mastered. Hence the initiation of the present work whose objective was to study the genetic and malecular anomalies of maxillo-mandibular odontogenic cysts and benign tumours by a review of the literature. Material and method: Search engines such as Pubmed, PMC, Google Scholar, Science direct, Journal of oncology were searched using key words with some filters. Results: Out of a total of 162 articles consulted, 40 were retained. The analysis of the articles retrieved allowed us to gather the genetic and molecular anomalies involved in the pathogenesis and development of benign maxillomandibular odontogenic cysts and tumours, sometimes explaining the clinical behaviour of some of these lesions. In addition to the molecular and genetic alterations encountered in the key genes of odontogenesis, molecules inhibiting the activities of apoptosis proteins would be hyper-expressed in certain very aggressive odontogenic lesions with a recurrence capacity. Conclusion: Knowledge of the molecular mechanisms involved in the pathogenesis and development of odontogenic lesions would allow the use of new therapeutic procedures in management of maxillo-mandibular odontogenic lesions.